Critérios de seleção de aeroportos para o transporte de frutas: evidências a partir da exportação de manga - Lotti, Raoni Luis Olmos (2017)
Time and cost are some of the criteria involved in decision making related to transportation. Although the literature shows these criteria as relevant in airport choice, note a lack of studies relating time and cost as criteria in the choice of cargo airports. In this sense, this study makes an analysis of the process of choosing airports for export of mango, identifying the criteria used, as well as the relationship between the criteria and the impact of the decision based on the prioritization of one criterion over the other. For this, through the AHP – Analytic Hierarchy Process method, indicators related to time and cost were compared, from interviews, performed with Brazilian mango exporters. From the selection criterion pointed out by exporters of mango, was simulated the choice between Brazilian airports most used for export the fruit in recent years. The results show that the prioritization of choice by the time, commonly used as a reference, can result in loss of road freight, increasing a 23% the costs with access to the airport terminal. In this sense, future studies can be conducted with the purpose to verify the relation between cost and time, in the decisions of choice between cargo airports involving nonperishable products.